Electrocatalytic reactivity of imine/oxime-type cobalt complex for direct perfluoroalkylation of indole and aniline derivatives. Issue 22 (27th May 2020) - Cui, Luxia; Ono, Toshikazu; Morita, Yoshitsugu; Hisaeda, Yoshio
Abstract : Imine/Oxime-type cobalt complex-catalyzed direct perfluoroalkylation of indole and aniline derivatives with nonafluorobutyl iodide ( n -C4 F9 I) under mild electrochemical method was demonstrated. Abstract : Imine/Oxime-type cobalt complexes, regarded as simple vitamin B12 model complexes, were utilized as catalysts for direct C–H perfluoroalkylations of indole and aniline derivatives with nonafluorobutyl iodide ( n -C4 F9 I) as the readily available perfluoroalkyl source. The synthetic approach described herein was performed under mild reaction conditions driven by controlled-potential electrolysis at −0.8 V vs. Ag/AgCl in organic solvents. The mechanistic investigations suggest that a nonafluorobutyl radical is mediated by homolytic cleavage of the cobalt(iii )–carbon bond in the catalytic cycle. This is the first report concerning a fluoroalkylation reaction of (hetero)aromatics catalyzed by the simple vitamin B12 model complex. The convenient electrocatalytic method employing a simple cobalt complex provides a facile synthesis method toward novel fluoroalkylated compounds, demonstrating potential applications in the fields of pharmaceutical chemistry and materials science.